THE INFLUENCE OF WORK DEMANDS ON WORK STRESS THROUGH INTRINSIC MOTIVATION AS INTERVENING VARIABLES - Andhy Tri Adriyanto; Arini Novandalina (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This research aimed to determine on the influence of work demands on work stress with intrinsic motivation as an intervening variable in Demak Regency. The population used the staff of the Demak District Education and Training Personnel Board. The sample had taken from 48 respondents. The research data came from two sources, i.e primary data and secondary data. This type of research was quantitative. These sampling used the purposive random sampling technique. The collected data were analyzed using Structural Equation Modeling (SEM) with SmartPLS ver 3.29 software. The results of this study had the work demands that made a negative influence on intrinsic motivation while intrinsic motivation had the significant of positive influence on the work stress. On the other hand, work demands had the significant of positive influence on work stress while intrinsic motivation could not mediate the influence of work demands on work stress.